Complement to the flora of Vietnam of the new species Kandelia obovata Sheue, Liu & Yong (based on signs of morphology and structure of production organs) - Hong Lien, Nguyen Thi; Thanh, Le (Academia Journal of Biology, 2014)
In the past years, it was believed that there is only one species Kandelia candel (L.) Druce under genus Kandelia belonged to Rhizophoraceae family. This species distributed widely, and they can be found in any in mangrove forests in the world. However, in 2004, some scientists found that there are two different Kandelia chromosome sets. A research on the morphology and structure of reproduction organs of two populations in North and South of Viet Nam has been conducted. Research results indicate that those population of Kandelia show differences in morphological characteristics, leaf structure, epidermis and stoma. Stoma density K. obovata is much more than those of K. candel. Cell numbers located around stoma are different in these species. Although stoma cell of two species look like pisiform but stoma cell cells around stoma of K. candel are arranged in circle order and those of K. obovata are arranged in ovan order. K. obovata is histionic distributive in a whole leaf double-side (have upper palisade tissue and underside palisade tissue) and K. candel palisade tissue class number K. candel less and have on-lied in upside, underside is had not. Structure sterm of two species also different, especial in who structure secondary qualities. The number of wood-fibre in textural component of K. candel more than K. obovata; vascular bed size of K. obovata larger than K. candel. Structure leaf-impression of two species are also differents. With author group what Sheue, Liu and Yong found along with our research results there in before we confirm that in Vietnam has K. obovata and K. candel.